2022
DOI: 10.3390/vaccines10040505
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Immune Response Elicited by Gold Nanoparticle- Based Nanovaccines against Infectious Diseases

Abstract: The use of nanoparticles for developing vaccines has become a routine process for researchers and pharmaceutical companies. Gold nanoparticles (GNPs) are chemical inert, have low toxicity, and are easy to modify and functionalize, making them an attractive choice for nanovaccine development. GNPs are modified for diagnostics and detection of many pathogens. The biocompatibility and biodistribution properties of GNPs render them ideal for use in clinical settings. They have excellent immune modulatory and adjuv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 141 publications
0
9
0
Order By: Relevance
“…Despite its wide range of functionalization capacity, the safety of gold nanoparticles remains an obstacle. As gold nanoparticles can accumulate in specific organs such as the liver and spleen in the long term, the distribution of gold nanoparticles and toxicity of accumulated gold nanoparticles in various cell types should be addressed 186 , 187 .…”
Section: Nanotechnology-assisted Covid-19 Mucosal Vaccinementioning
confidence: 99%
“…Despite its wide range of functionalization capacity, the safety of gold nanoparticles remains an obstacle. As gold nanoparticles can accumulate in specific organs such as the liver and spleen in the long term, the distribution of gold nanoparticles and toxicity of accumulated gold nanoparticles in various cell types should be addressed 186 , 187 .…”
Section: Nanotechnology-assisted Covid-19 Mucosal Vaccinementioning
confidence: 99%
“…Low toxicity, chemical inertness, biocompatibility, and biodistribution properties have made metallic nanoparticles, in particular gold nanoparticles (AuNPs), excellent candidates for the development of nanovaccines during last years. A very recent review by Sengupta et al [ 50 ], shows the role of AuNPs for the formulation of nanovaccines against various infectious agents, including viral agents. Teng at al.…”
Section: Metal Complexes In Antiviral Vaccinesmentioning
confidence: 99%
“…Au NPs has shown potential in cancer therapy as drug carriers and recently as radiosensitizers in photothermal and photodynamic therapy [ [5] , [6] , [7] ]. Au NPs has also been exploited in antiviral therapy for their adjuvant effect for vaccines or as delivery systems of antiviral drug [ 8 , 9 ]. Some of the recent studies has also demonstrated Au NPs possessing antiviral properties against various viruses [ 7 , 10 ] (e.g.…”
Section: Introductionmentioning
confidence: 99%